Fringe-dependent notch activation and tramtrack function are required for specification of the polar cells in Drosophila oogenesis. - Althauser, C.; Jordan, K.C.; Deng, W.M.; Ruohola-Baker, H. (Developmental Dynamics, 2005)
During Drosophila oogenesis, each egg chamber is encapsulated through the coordinated signaling of multiple pathways, resulting in the formation of polar cells at the termini and a row of stalk cells in between each egg chamber. Notch signaling is required for specification of a precursor group containing both stalk and polar cells. Together, the Notch and JAK/STAT pathways specify the stalk cells as well as a group of prepolar cells, from within that group. The mechanism by which the polar cells differentiate from the prepolar group involves apoptosis, but the pathways which control that process are largely unknown. We now demonstrate that Notch signaling, activated by Delta and transduced by the transcription factor Tramtrack, is involved in the process of refining the prepolar cell group to two polar cells. The glycosyltransferase Fringe is expressed and required cell-autonomously in prepolar cells for this process. However, the transcription factor Mirror, which inhibits fringe expression in other tissues and stages of development, as well as Serrate, one of the two known ligands for Notch, are not required for maturation of prepolar cells. This finding suggests that Fringe is necessary for generating positional information in localizing a high-affinity interaction between Notch and its ligand Delta, even if a second ligand is not essential.